1002 Circadian Misalignmentand Weekend Alcohol Use In Late Adolescent Drinkers. (27th April 2018) - Hasler, B P; Ngari, W; Clark, D B
Abstract: Introduction: Adolescents often suffer from circadian misalignment (or social jet lag) due to a mismatch between their typically-later circadian timing and early class times. Sleep/circadian disturbances have been linked to increased substance involvement, but few studies have employed objective circadian measures. Here, we assessed the proximal relationships between objective measures of circadian alignment and self-reported alcohol use in a sample of late adolescent drinkers. Methods: Participants included 31 late adolescents (18–22 y/o; 19 females) reporting weekly drinking. Participants reported past day's alcohol use each morning via smartphone and wore wrist actigraphs for 13 days. Participants completed pre-/post-weekend circadian phase assessments (Thursday and Sunday) via the dim light melatonin onset (DLMO). Sleep/circadian variables included the DLMO-midsleep phase angle (Thursday and Sunday), as well as weekday-weekend differences in midsleep and DLMO, respectively. Alcohol variables included baseline alcohol use and binge days (past month), as well as weekend alcohol use (sum of Friday/Saturday). Results: Mean alcohol use was 33.4 drinks and 3.5 binge days (past month) and 6.0 drinks (study weekend). Mean Thursday and Sunday DLMOs were 22:03 ± 1:28 and 22:11 ± 1:20, respectively. Mean weekday and weekend midsleep times were 4:54 ± 1:02 and 5:29 ± 1:03, respectively. Mean weekday and weekend DLMO-midsleep phase angles were longer than previously reported in healthy samples ( 6 h) at 6.9 and 7.2 h, respectively. Midsleep timing averaged 0.5 h later on weekends relative to weekdays (range=1.1 h earlier to 4.8 h later). Unexpectedly, weekend DLMO timing was not significantly later (mean=0.1 h later; range=1.4 h earlier to 1.8 h later). In contrast to predictions, sleep/circadian variables were generally uncorrelated with alcohol use measures. Later Thursday DLMOs and greater baseline binge alcohol use showed a trend-level correlation (r=0.34, p=0.06). Conclusion: Findings did not support hypothesized associations between circadian misalignment and weekend alcohol use, perhaps obscured by the high levels of normative drinking in this age group. In contrast to typical social jet lag, many participants advanced in circadian phase over the weekend, highlighting the complexity of sleep-wake schedules in this age group. Support (If Any): Grants from NIH: R21AA023209 (Hasler) and K01DA032557 (Hasler).